Evaluation of nutritional status and the food habits of officials of a university institution in the west of Santa Catarina - Tonini, Elione; Broll, Ana Maria; Nappi Corrêa, Elizabeth (O Mundo da Saúde, 2013)
This study has for aim to value the nutritional status and the food habits of the officials of an highest school institution in the west of Santa Catarina. The descriptive study, was developed in the second semester of 2008, in Chapecó-SC city. The example was compost by 15% of the population to be investigated, divided between teachers and administrative technical. A questionnaire compost by 6 questions, was applied approaching the food habits, also anthropometric data (weight and height) was collected to calculate the Body Mass Index and subsequent classification of the nutritional status. The average age of the interviewed public was 33.7 years (± 10.6), showing more people with obesity and overweight, between the teaches and the administrative technical of 39.3%. Of the interviewed, 87.6% work 40 hours weekly, staying 2 or more turns in the institution. It was also found that the more consumed food by the interviewed was roast snacks, salty meals black coffee and soda, consumed by 40% or more of the interviewed. With the respect of the alimentation quality did in the work place, only 10.8% of the interviewed consider the alimentation adequate. Concluding, that most of the interviewed officials are unsatisfied with the food served in the commercialization areas in the campus. As improvement suggestions was appointed that the availability of a greater variety of foods considered healthy, the diversification of the commercialization areas and the “potencializaçao” of the “agroecologia” fair, would be good alternatives, beside the presence of a professional nutritionist as a decisive factor in the quality of food served.